Reliability of sagittal plane hip, knee, and ankle joint angles from a single frame of video data using the GAITRite camera system. (January 2015) - Ross, Sandy A.; Rice, Clinton; Von Behren, Kristyn; Meyer, April; Alexander, Rachel; Murfin, Scott
Abstract The purpose of this study was to establish intra-rater, intra-session, and inter-rater, reliability of sagittal plane hip, knee, and ankle angles with and without reflective markers using the GAITRite walkway and single video camera between student physical therapists and an experienced physical therapist. This study included thirty-two healthy participants age 20–59, stratified by age and gender. Participants performed three successful walks with and without markers applied to anatomical landmarks. GAITRite software was used to digitize sagittal hip, knee, and ankle angles at two phases of gait: (1) initial contact; and (2) mid-stance. Intra-rater reliability was more consistent for the experienced physical therapist, regardless of joint or phase of gait. Intra-session reliability was variable, the experienced physical therapist showed moderate to high reliability (intra-class correlation coefficient (ICC) = 0.50–0.89) and the student physical therapist showed very poor to high reliability (ICC = 0.07–0.85). Inter-rater reliability was highest during mid-stance at the knee with markers (ICC = 0.86) and lowest during mid-stance at the hip without markers (ICC = 0.25). Reliability of a single camera system, especially at the knee joint shows promise. Depending on the specific type of reliability, error can be attributed to the testers (e.g. lack of digitization practice and marker placement), participants (e.g. loose fitting clothing) and camera systems (e.g. frame rate and resolution). However, until the camera technology can be upgraded to a higher frame rate and resolution, and the software can be linked to the GAITRite walkway, the clinical utility for pre/post measures is limited.